2017
DOI: 10.12693/aphyspola.132.599
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Wear Strength of Blast Furnace Slag Blended Polymer Materials

Abstract: Having symmetrical and balanced material properties, polymer matrix composites are increasingly becoming popular due to easiness of construction and are use in the production of aerospace and automotive structures. In the study, we developed polymer composites based on epoxy resins, containing up to 40 wt.% of blast furnace slag and determined their pin-on-disc dynamic friction, wear, Shore hardness and surface roughness values. Wear tests were performed using a pin-on-disc under dry friction conditions, at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Hence, waste generated from different industries can be established as a potential filler material for polymer composite. Though a considerable amount of work has been performed by the scientific community in the utilization of industrial waste as filler in a polymeric resin 5–19 . Among the various waste generated from different industries, few of them are generated in huge quantities and are of great concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, waste generated from different industries can be established as a potential filler material for polymer composite. Though a considerable amount of work has been performed by the scientific community in the utilization of industrial waste as filler in a polymeric resin 5–19 . Among the various waste generated from different industries, few of them are generated in huge quantities and are of great concern.…”
Section: Introductionmentioning
confidence: 99%
“…Though a considerable amount of work has been performed by the scientific community in the utilization of industrial waste as filler in a polymeric resin. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Among the various waste generated from different industries, few of them are generated in huge quantities and are of great concern. Blast furnace slag, red mud, copper slag, fly ash, LD slag, and LD sludge are among them.…”
mentioning
confidence: 99%
“…This material is widely used in concrete to improve its mechanical properties, stability, and durability . Only a few studies on the use of BFS as filler in polymer composites are available in the literature . Gunes et al .…”
Section: Introductionmentioning
confidence: 99%
“…Based on the fact that naturally occurring minerals, such as kaolin, clay, and feldspar, are widely used in the polymer‐based composites , it could be concluded that slag which is a mixture of oxides could also used as a reinforcement for polymer composites. In this regard, only few studies on the use of slag as filler in polymer composites are available in the literature . For example, it has found that slag was able to improve the tribological properties of an epoxy composite .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, only few studies on the use of slag as filler in polymer composites are available in the literature . For example, it has found that slag was able to improve the tribological properties of an epoxy composite . Furthermore, few studies on the use slag in polymeric foams for high‐voltage insulation are available and polyurethane foams seem to be a good candidate for this application .…”
Section: Introductionmentioning
confidence: 99%